A Highly Dense Genetic Map for Ginkgo biloba Constructed Using Sequence-Based Markers - Liu, Hailin; Cao, Fuliang; Yin, Tongming; Chen, Yingnan (Frontiers in Plant Science, 2017)
Ginkgo biloba L. is a well-known living gymnosperm fossil that has medicinal and ornamental value. In this study, a high density genetic map was constructed with megagametophytes of 94 seeds from a single Ginkgo tree by employing the specific length amplified fragment (SLAF) sequencing technique. The average sequencing depth was 11.20×, which yielded 538,031 high-quality SLAFs. Among these SLAFs, 204,361 were heterozygous in the maternal tree and segregated in the progeny. The established map contained 12,263 SLAFs that were assigned to 12 linkage groups. The number of linkage groups on this map equaled the number of chromosomes in Ginkgo. The total map length was 1,671.77 cM, with an average distance of 0.89 cM between adjacent marker bins. Map evaluation based on the haplotype map and the heat map validated the high quality of the established map. Because Ginkgo is an economically and biologically important tree, strenuous efforts have been exerted to sequence its genome. This new map, built using sequence-based markers, will serve in the future as a fundamental platform for anchoring sequence assemblies along Ginkgo chromosomes. This map also provides a desirable platform for various genetic studies of Ginkgo, including gene/quantitative trait locus mapping and marker-aided selection.